Auditory Threshold Variability in the SAMP8 Mouse Model of Age-Related Hearing Loss: Functional Loss and Phenotypic Change Precede Outer Hair Cell Loss - Peixoto Pinheiro, Barbara; Adel, Youssef; Knipper, Marlies; Müller, Marcus; Löwenheim, Hubert (Frontiers in Aging Neuroscience, 2021)
Age-related hearing loss (ARHL) is the most common sensory deficit in aging society, which is accompanied by increased speech discrimination difficulties in noisy environments, social isolation, and cognitive decline. The audiometric degree of ARHL is largely correlated with sensory hair cell loss in addition to age-related factors not captured by histopathological analysis of the human cochlea. Previous studies have identified the senescence-accelerated mouse prone strain 8 (SAMP8) as a model for studying ARHL and age-related modifications of the cochlear redox environment. However, the SAMP8 population exhibits a large variability in auditory function decline over age, whose underlying cause remains unknown. In this study, we analyzed auditory function of SAMP8 mice by measuring auditory brainstem response (ABR) thresholds at the age of 6 weeks (juvenile), 12 weeks (young adult), and 24 weeks (adult). Consistent with previous studies, SAMP8 mice exhibit an early progressive, age-related decline of hearing acuity. However, a spatiotemporal cytohistological analysis showed that the significant increase in threshold variability was not concurrently reflected in OHC loss observed in the lower and upper quartiles of the ABR threshold distributions over age. This functional loss was found to precede OHC loss suggesting that age-related phenotypic changes may be contributing factors not represented in cytohistological analysis. The expression of potassium channels KCNQ4 (KV7.4), which mediates the current IK,n crucial for the maintenance of OHC membrane potential, and KCNQ1 (KV7.1), which is an essential component in potassium circulation and secretion into the endolymph generating the endocochlear potential, showed differences between these quartiles and age groups. This suggests that phenotypic changes in OHCs or the stria vascularis due to variable oxidative deficiencies in individual mice may be predictors of the observed threshold variability in SAMP8 mice and their progressive ARHL. In future studies, further phenotypic predictors affected by accumulated metabolic challenges over age need to be investigated as potentially underlying causes of ARHL preceding irreversible OHC loss in the SAMP8 mouse model.